Financial Performance Analysis of Selected Private Sector Banks in India - K.Rajarajeswari; Dr. S.B. Gayathri (International Journal of Engineering and Management Research, 2018)
The performance of the banking system has been widely recognized as an important element for economic growth and for enhancing the economic and financial system buoyancy in facing financial crisis. In fact, such a vital role in the economy has made banks to be considered as one of the most strained kinds of businesses in the globe as they are subject to close scrutiny since banks will otherwise be counterproductive and severely damage the economy of a country. Efficient and profitable banks maximize shareholders’ value and encourage the shareholders to make additional investments. As a result of which, more employment opportunities will be created and more goods and service will be produced and ultimately bring about economic growth in which private and public sector banking institutions play equal role. The present study analyses the financial performance of selected private banks in India with the help of correlation analysis by considering return on total assets as the independent variable.